PENATALAKSANAAN AWAL KEJANG DEMAM PADA ANAK DI POLI ANAK RUMAH SAKIT BHAYANGKARA SURABAYA - MAIL, ERFIANI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
Febrile seizures are still very common in children. The incidence of febrile seizures in various developed countries such as the United States and Western Europe reaches 2 - 4% whereas in developing countries the number of sufferers is higher. Approximately 20% of patients suffer from complex seizures that must be treated more diliti. The incidence of febrile seizures in Indonesia mainly occurs in children aged 6 months to 4 years. Almost 3% of children aged under 5 years have experienced febrile seizures.                The type of research used is descriptive research. Descriptive research is a study that aims to describe (describe) urgent events that occur in the present. Variable in this research is mother knowledge about initial management of febrile seizures. In this study, the sample is a mother who has children diagnosed with febrile seizures as many as 34 respondents This study was conducted in Poly AnakBhayangkara Hospital Surabaya. The study was conducted on 18 February - 5 March 2013. The instrument used was kuesiner. Instrument has been done Test validity and reliability by using Pearson Product Moment formula and reliability test by using Cronbach Alfa in SPSS program.                The result of research from the age factor that more than 50% of respondents aged 20-30 years are 21 respondents (61,8%), while the result of research of education factor can know that most of respondent of SMA education is 14 responden (41,2%), from work factors that more than 50% of respondents did not work ie 20 respondents (58.8%), from the information factor that most respondents have been informed about the initial management of febrile seizure is 26 respondents (76.5%), from information sources can it is known that most respondents get information from Radio / TV respondents (26.5%), from the knowledge factor can be seen that most respondents have good knowledge that is 16 respondents (47%), knowledge known that most respondents have good knowledge that is 16 respondents (47%). Knowledge is the result of knowing and this happens after people do sensing a particular object. So Knowledge of respondents about febrile seizures obtained respondents after doing a lot of reviews both from information sources (newspapers, magazines, television, health workers, and others) as well as from the personal experience of respondents. It can be concluded that the knowledge of mother about the initial management of febrile seizures in Poly AnakBhayangkara Surabaya Hospital on February 18th - March 5th 2011 most of the respondents have good knowledge that is 16 respondents (47%). Keywords: Knowledge, febrile seizures